IMPLIKASI BANTUAN OPERASIONAL SEKOLAH (BOS) BUKU TERHADAP KREATIVITAS GURU MENULIS BUKU MODUL - Isharijadi Isharijadi (Jurnal Pendidikan, 2008)
This  research  serves  an analysis  as to empirically   explain  the implementation    of School Operational Grant  (BOS)  for books from government and  its relevance   towards  the teachers' creativeness in writing   books  and  modules.   School  Operational   Grant  for books  is intended    to  ease   students’ parents   in  providing    books   for  their children.Teachers, as the front-liners for the students' learning development, are attempted to creatively provide the  sufficient learning  resources, one of which is done by  arranging    subject modules.    The   teachers    are  obliged   for  arrangement    of  learning modules,   because  through  the modules  they can render  creativeness and material   development   for students  based  on the development   of the  market  share  and lack of teachers' works.Under  empirical  observation  done by the researcher,  it is found that the School Operational  Grant for books arises dilemma for teachers and public  in terms that  1) teachers  face difficulties  to distribute  their works/modules   in substitution  for books from BOS, 2) the demand  for teachers'    modules   and books  becomes   students'   parents  burden,  3) the distribution   of the grant books which needs very  strict supervision from  the authority.